2016
DOI: 10.1111/jpn.12480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of realimentation after nutrient restriction during mid‐ to late gestation on pancreatic digestive enzymes, serum insulin and glucose levels, and insulin‐containing cell cluster morphology

Abstract: This study examined effects of stage of gestation and nutrient restriction with subsequent realimentation on maternal and foetal bovine pancreatic function. Dietary treatments were assigned on day 30 of pregnancy and included: control (CON; 100% requirements; n = 18) and restricted (R; 60% requirements; n = 30). On day 85, cows were slaughtered (CON, n = 6; R, n = 6), remained on control (CC; n = 12) and restricted (RR; n = 12), or realimented to control (RC; n = 11). On day 140, cows were slaughtered (CC, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…Studies evaluating fetal programming of digestive enzymes have largely focused on changes in the level of DM intake of the dam through various periods of gestation. Maternal dietary restriction of beef cows during early- or early-to-mid-gestation and then realimentation to maintenance intake during late-gestation increased fetal pancreatic α-amylase per gram of protein by 3.0- and 4.1-fold, respectively ( Figure 1 ); [ 36 ]. Furthermore, fetal pancreatic α-amylase per gram of protein was not influenced when cows were restricted during either early or early-to-mid-gestation.…”
Section: Influence Of Prenatal Nutrition On Fetal Carbohydrase Actmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating fetal programming of digestive enzymes have largely focused on changes in the level of DM intake of the dam through various periods of gestation. Maternal dietary restriction of beef cows during early- or early-to-mid-gestation and then realimentation to maintenance intake during late-gestation increased fetal pancreatic α-amylase per gram of protein by 3.0- and 4.1-fold, respectively ( Figure 1 ); [ 36 ]. Furthermore, fetal pancreatic α-amylase per gram of protein was not influenced when cows were restricted during either early or early-to-mid-gestation.…”
Section: Influence Of Prenatal Nutrition On Fetal Carbohydrase Actmentioning
confidence: 99%
“…Interestingly, intestinal glucose transport also has been shown to differ between cattle and sheep [ 13 ]. However, it should be noted that when Keomanivong et al [ 36 ] found a programming response of fetal pancreatic α-amylase, maternal dietary restriction occurred during early or early- to mid-gestation. In general, organogenesis occurs during early-to-mid-gestation [ 3 ] and thus, functional alteration of fetal gastrointestinal organs may be more severe during early gestational nutrient restriction.…”
Section: Influence Of Prenatal Nutrition On Fetal Carbohydrase Actmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative sample of the body of the pancreas was immersion-fixed in formalin and embedded in paraffin blocks with proper and persistent orientation, and immunohistochemistry was performed as described previously [3,22]. Tissues were cut (5-μm sections), mounted on slides, deparaffinized and rehydrated.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Nutrient restriction during late gestation may also influence fetal digestive enzymes as total fetal pancreatic trypsin content and α-amylase activity decrease with 60% of maternal nutrient restriction but there is no effect on fetal carbohydrase, glucoamylase, maltase, or isomaltase activities (TROTTA et al, , 2021. Keomanivong et al (2017) also found a decrease in α-amylase activity but no effects on pancreatic digestive enzymes.…”
Section: Fetal Organ Developmentmentioning
confidence: 95%